Parent/Student Risk and Protective Factors in Understanding Early Adolescent's Body Mass Index. (May 2016) - Fitzpatrick, Kevin M.; Willis, Don
This article's aim is to examine correlates of middle school students' body mass index (BMI). Little research simultaneously has considered both child and parent correlates in predicting child's BMI; we examine the interrelationships between middle school students and their parent's risks and protective factors and their impact on the child's BMI. The study is based on a cross-sectional survey of 161 parent-middle school child pairs living in a large school district in Northwest Arkansas. The analysis finds that while parent BMI is an important correlate of student BMI, other parental risks and even parental protective factors' impact on student BMI were, in part, minimized by the risk and protective factors of students. Important differences emerged between parent and child correlates of student's BMI scores. More comprehensive joint assessments of parent and child social contexts and their role in determining weight status seem clearly warranted from this exploratory analysis.